PENENTUAN AKTIVITAS ANTIBAKTERI EKSTRAK ISOLAT FUNGI ENDOFIT DARI DAUN GALING-GALING (Cayratia trifolia L) - Ayyub Harly Nurung; Fitriana Fitriana; Herwin Herwin (Fakultas Farmasi UMI, 2022)
Utilization of wild plants around us needs to be done to expand the chances of wild plants being used as traditional medicine. These plants have the main content of the active compounds in the form of steroids, terpenoids, flavonoids, tannins and is reported to have antibacterial activity. This research aims to determine the concentration of endophytic fungi isolates IDGG 02, IDGG 03 and IDGG 06 from the leaves of galing-galing (Cayratia trifolia L). The first stage purification isolates of endophytic fungi in order to obtain single isolates. Then fermented using a shaker for 21 days at room temperature. Fermented extracted with ethyl acetate solvent using a liquid-liquid extraction methods to obtain a dry extract. Testing the minimum inhibitory concentration (MIC) with concentrations of 2048, 1024, 512, 256, 128, 64, 32, 16, 8 and 4 µg / mL and testing for antibacterial activity using agar diffusion methods against bacteria Staphylococcus aureus, Staphlococcus epidermidis, Escherichia coli and Vibrio cholerae.The results obtained MIC 2048 MIC ug / mL to extract isolates IDGG 02 and IDGG 06, while the extract obtained 03 isolates IDGG 1024 MIC ug / ml against all bacteria. Results of testing the antibacterial activity of endophytic fungi isolated extract IDGG 02, 03 IDGG produce diameter zone of inhibition at a concentration of 2048 mg / mL against Staphylococcus aureus, Staphlococcus epidermidis, Escherichia coli and Vibrio cholerae.